The Impact of Territorial Conflict in the Himalayas on India-China Bilateral Relations in 2020-2023 - Khalifah, Nanda Putri; Susilowati, Ida (SALAM: Jurnal Sosial dan Budaya Syar-i, 2024)
In 2020, tensions escalated again between India and China in the disputed Central Sector area, especially in the Galwan Valley, Ladakh. This incident became one of the deadliest clashes in the history of the border conflict between the two countries, as it resulted in casualties on both sides. This study aims to analyze the dynamics of territorial conflict in the Himalayan Mountains region and its impact on bilateral relations between India and China. This study uses a qualitative research type with a descriptive method with a case study approach. Data analysis techniques include collection, reduction, processing, presentation, and drawing conclusions. The data used comes from academic journals, scientific articles, books, international documents, and related news reports. The results of the study show that the border conflict in the Himalayas has had a significant impact on the military, economic, international order, and ideology of India and China. In the military field, tensions between the two countries have increased, marked by the construction of defense infrastructure, an increase in the number of troops in the border area, and frequent incidents of clashes between the Indian and Chinese militaries. From the economic sector, this tension has caused the dynamics of bilateral trade and investment cooperation. In the international order, this conflict strengthens the dynamics of Asian geopolitics, with India strengthening cooperation through the Quadrilateral Security Dialogue (Quad) to balance China, while China strengthens its position through the Belt and Road Initiative (BRI). In the ideological field, this conflict encourages nationalist sentiments in both countries, which have an impact on their respective foreign policies and complicate the negotiation process to resolve border disputes. Thus, this study confirms that territorial conflicts in the Himalayas not only have implications for border security, but also affect bilateral relations more broadly, both in the fields of politics, economics, and global strategy. This study provides insight into how territorial conflicts between two neighboring countries can affect the dynamics of bilateral relations between the two which can disrupt regional stability.Keywords: Geopolitics; Territorial Conflict; Himalayas; China; India